Investigation of cis-trans isomer dependent dermatotoxicokinetics of UV filter ethylhexyl methoxycinnamate through stratum corneum in vivo - Sharma, Anežka; Bányiová, Katarína; Vrana, Branislav; Justan, Ivan; Čupr, Pavel (Environmental science and pollution research international, 2017)
2-Ethylhexyl methoxycinnamate (EHMC) is one of the most used ultraviolet filters in personal care products. It undergoes cis/trans isomerization in sunlight, and there is limited toxicological understanding of the effects of the cis-isomer. It is known that two geometric isomers of one compound can have different physico-chemical properties and effects. However, there are no studies focusing on toxicokinetics of EHMC isomerization products to compare their potential difference in dermal exposure to cis-EHMC and trans-EHMC due to the difference in their dermatotoxicokinetics. In this study, dermal absorption of the parental trans-EHMC and its cis isomer was studied. A commercially available sunscreen lotion containing trans-EHMC and spiked with laboratory-prepared cis-EHMC was locally applied on the forearm skin of two volunteers. After 8 h of skin exposure, the stratum corneum (SC) layer was removed by tape stripping. The removed thickness of the SC was determined spectrophotometrically using a total protein assay. The concentration of both isomers in the removed SC was measured by HPLC-DAD. A new diffusion and permeability coefficient of both EHMC isomers in SC were determined by Fick's second law of diffusion in vivo. The difference in dermatotoxicokinetic parameters between the two isomers was not statistically significant. However, separate toxicological studies of isomeric forms and the determination of their dermatotoxicokinetic parameters are crucial for refinement of human risk assessment.
Keywords: Toxicokinetics; dospělí; Human skin permeation; epidermis; Female; Epidermis; přípravky chránící proti slunci; Adult; toxikokinetika; Sunscreening Agents; ženské pohlaví; Skin Absorption; lidé; Stereoisomerism; kožní absorpce; stereoizomerie; cinnamáty; Dermatotoxicokinetics; Cinnamates; Ethylhexyl methoxycinnamate; Cis/trans isomerization; Tape stripping; Personal care products; Humans